Reading Comprehension Strategies: A Narrative Review - Tarique; M. Anthony, Elizabeth (Development in Language Studies, 2022)
Learning and teaching a second language is always great fun and complex phenomenon that needs so much from the instructor and learner to involve in the process to get the maximum outcomes. Reading is essential for academic and personal growth and an equally important tool for learning. Hence, this study aimed to investigate the reading strategies and difficulties experienced by tertiary learners of English as a Second language. The primary source for collecting the data was published studies taken from Google Scholar; the recent studies have been gone through for the article; using the following keywords: Reading, reading strategies, and stages of reading. The findings suggest that less attention has been paid to the reading skills by the language teachers while teaching the target language to the learners. In addition, the learners and teachers do not conceive the reading skills as the essential and crucial part of teaching and learning a second language. Based on the findings of this study, it concluded that reading is one of the very basic skills of languages that enhance the capability of the learners to understand other parts and skills of the Language.